Training of Operating Video Conference for Online Learning During Covid-19 - Heni Rita Susila; Arief Qosim; Edi Sutiono (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Lecturers required to have more capabilities in using technology as a facilitate in doing instructional process. In Covid-19 era, Indonesian Government enforced all level of education to use online learning method to prevent the spread of the disease. This policy also applies to university level education. Online learning is the only possible chosen method to keep continue the learning process as a substitute of offline learning. Facing this situation, lecturers need to upgrade their skill in using some software application to support online learning method, especially skill in operating video conference software application. Need assessment result showed that only 40% lecturers have capability in operating video conference software application. This article aims to describe the utilization of technology as a supporting system in online learning especially using vide conference to facilitate instructional process. The author uses a qualitative approach with a descriptive model in which the data and exposure presented in this paper sourced from the training. Data collection is taken by interviewing and distributing questionnaires. A training of operating video conference application and using LMS for online learning was held for lecturers in Baturaja University. The result shows that participants feel satisfied and get benefit from the implementation of this training.